Traffic and Granular Flow’01 2003
DOI: 10.1007/978-3-662-10583-2_46
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations of a Driven Granular System under Gravity

Abstract: Molecular dynamics study on the granular bifurcation in a simple model is presented. The model consists of hard disks, which undergo inelastic collisions; the system is under the uniform external gravity and is driven by the heat bath. The competition between the two effects, namely, the gravitational force and the heat bath, is carefully studied. We found that the system shows three phases, namely, the condensed phase, locally fluidized phase, and granular turbulent phase, upon increasing the external control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These facts showed that if ðN; r c Þ and G are fixed, the macroscopic properties are determined as a certain fixed value for any ðg; v; A 0 Þ. Actually, many previous studies (including the works of authors in microgravity [5,6]) have been performed by using CRC for its simplicity. However, in experimental and theoretical works, it is generally known that the restitution coefficient strongly depends on the impact velocity v imp (e.g.…”
Section: Introductionmentioning
confidence: 94%
“…These facts showed that if ðN; r c Þ and G are fixed, the macroscopic properties are determined as a certain fixed value for any ðg; v; A 0 Þ. Actually, many previous studies (including the works of authors in microgravity [5,6]) have been performed by using CRC for its simplicity. However, in experimental and theoretical works, it is generally known that the restitution coefficient strongly depends on the impact velocity v imp (e.g.…”
Section: Introductionmentioning
confidence: 94%